The Effect of the Harzándlér's Sibling Magomini on the Subject (European Journal of Economics, Finance and Business Development, 2024)
The article highlights the important aspects of child development and, later, how few places they find in social processes and cooperate. The article also outlines the scientific research of psychologists on sibling relationships.